Shale oil potential of the Upper Cretaceous in the Changling area, Southern Songliao Basin, NE China: perspectives of geochemistry and petrology. (2016) - Zhou, Sandong; Tang, Jiguang; Liu, Dameng; Cai, Yidong
The geochemistry and petrology of the Upper Cretaceous Qingshankou and Nenjiang organic-rich shale from the Changling area (CLA) of the southern Songliao Basin located in NE China were investigated to evaluate the shale oil potential. The organic-rich shale ranges from 30 m to 115 m in total thickness, contains kerogen type I and II, and has a total organic carbon (TOC) content of 0.5 wt. % to 11.1 wt. %, with relatively high S1, S2 and hydrogen index (HI). The random vitrinite reflectance (Ro, r ) varies from 0.52% to 1.07%, which is in the early-medium thermal evolution stage. The hydrocarbon (HC) potential (S1 + S2 ) / TOC × 100 generally increases with the burial depth in K2 n, while there is no clear correlation between HC potential and burial depth in K2 q. The S1 and chloroform bitumen ('A') increase with increasing TOC, which can be divided into three groups: a stable low section, a rising section and a stable high section. Appropriate burial depth, stabilised geological structures and low gas-oil ratio (100-118 m 3 /t) are favourable for shale oil preservation. From the perspectives of oil generation and storage, the prospective shale oil targets were acquired, which could be divided into three levels. The results show that the amounts of shale oil associated with the K2 q and K2 n Formations in the CLA is 9.617 × 10 8 t. The most favourable target areas of shale oil were primarily located at the Chaganhua town and around the Well Y5. [Received: August 10, 2015; Accepted: March 3, 2016]